Assessing inter-basin groundwater input to the Verlorenvlei estuarine lake using stable isotopes and hydrochemistry - A. Welham; J. van Rooyen; A. Watson; J. Miller; R. Chow (Journal of Hydrology: Regional Studies, 2025)
Study region: Verlorenvlei Catchment (∼1 890 km2) is an agriculture-dominated area (∼43 % per km2) on South Africa’s west coast. This semi-arid region has variable rainfall and high evaporation rates, affecting the three major aquifers and Verlorenvlei – a RAMSAR-listed estuarine lake. Study focus: Natural processes (i.e., extended dry periods and evaporation) and anthropogenic activities (i.e., agricultural expansion and groundwater abstraction) have threatened Verlorenvlei’s ecological functions. Seasonal and spatial changes between the water sources (i.e., direct rainfall, surface water, and groundwater) supporting Verlorenvlei were determined using δ18O and δ2H isotopes and hydrochemical analyses. Inter-basin aquifer contribution was investigated to assist in explaining Verlorenvlei's slow recovery since the recent 2015 – 2018 Western Cape drought. New insights: A proportion of groundwater from outside the topographic and surface-water delineated catchment supports Verlorenvlei during the dry month of April (i.e., G30F Langvlei sub-catchment). Furthermore, Verlorenvlei experiences high evaporation (evaporation best fit line: δ2H = 12.49 x δ18O - 47.68, average δ2H value of 47.1 ‰ and average δ18O value of 7.64 ‰) compared to its feeding rivers. Two sandstone and shale-dominated sub-catchments exhibit overlapping groundwater δ18O and δ2H values and water types to the sub-catchment in the nearest vicinity of Verlorenvlei, suggesting a disproportionately high groundwater contribution from these sub-catchments to Verlorenvlei. Evaluation of Verlorenvlei’s water balance should consider both surface water and groundwater sources, particularly from inter-basin aquifer sources during prolonged droughts.